Effectiveness of the Four-Frequency Protocol of Repetitive Peripheral Magnetic Stimulation (rPMS) for Chronic Pain - Sanansilp V. (2023)
Objective: Repetitive peripheral magnetic stimulation (rPMS) is a noninvasive method of delivering a magnetic field to the periphery other than the brain. The treatment has shown positive outcomes for chronic pain and provides many advantages. This study investigated the effectiveness of the four-frequency protocol of rPMS in patients with chronic pain. Materials and Methods: A retrospective review was conducted of patients with chronic pain treated with the four-frequency protocol. Data on patient demographics, pain characteristics, quality of life, and satisfaction were collected and analyzed. Results: Forty-eight patients (174 sessions) were eligible for analysis. Most patients (81%) were diagnosed with chronic neuropathic pain. Upon completing the 4-week course of treatment, the mean ± SD of percentage of pain reduction was 49.7% ± 34.8%. The pain score also significantly decreased from baseline (mean difference, 3.3; 95% CI, 2.5-4.1; P < 0.001). Responses to treatment were observed for most patients (79.2%) and most treatment sessions (87.4%). For immediate effectiveness, the mean ± SD of percentage of pain reduction at the end of each treatment session was 46.2% ± 27.6%. Improvements in mood, function, and sleep were reported by 75.8%, 77.3%, and 79.5% of patients, respectively. Furthermore, most patients (72.5%) expressed satisfaction with the treatment. Conclusion: The four-frequency protocol of rPMS for patients with chronic pain significantly reduced their pain scores for immediate effect and after the 4-week treatment course. A positive treatment response, an improved quality of life, and satisfaction with the therapy were found for nearly 80% of the patients.